Um método numérico para a solução de problemas em física quântica de poucos corpos - Yamashita, M. T. [UNESP] (My University, 2008)
In this paper it is presented a numerical method that can be used by undergraduate students to solve quantum few-body problems in physics. The method is applied to a couple of two-body problems that are usually seen by students: the hydrogen atom and the deuteron. However, the method can be extended to three or more particles.
A numerical method to solve quantum few-body problems in physics
Keywords: Few-body problems; Variational method